Comparative study of social innovation programs and products in improving community welfare in Kopi Kang Garut and Sirih Sijale Tangerang - Nacita, Ada Senandung; Aprilia, Risa Dela; Arrozy, Ahmad Muhajid (Priviet Social Sciences Journal, 2026)
Corporate Social Responsibility (CSR) programs based on social innovation often succeed in strengthening community production capacity but continue to face challenges at the downstream stage, particularly in marketing, product diversification, and market access. This study aims to analyze the community empowerment process in the Kopi Kang CSR Program in Garut Regency and the Sirih Sijale Program in Tangerang City using Jim Ife’s empowerment theory. The research employs a qualitative approach with a descriptive comparative method. Data were collected through field observations, interviews with program managers and community members, and document analysis, then analyzed descriptively based on Jim Ife’s empowerment dimensions. The findings indicate that both programs have reached the early to intermediate stages of empowerment, as reflected in improved production capacity, utilization of local resources, and increased community participation. However, empowerment remains limited at the downstream level due to underdeveloped marketing strategies, restricted distribution networks, and limited product diversification, which result in segmented market reach. CSR involvement in marketing functions as transitional support to facilitate market access rather than as a form of economic dependency. This study concludes that the sustainability of social innovation–based CSR programs requires gradual strengthening of downstream capacities, particularly through adaptive product diversification and market expansion strategies, to enable communities to gain more comprehensive and sustainable control over the value chain.